The (in)visibility of value : a Wittgensteinian perspective - Kumar Tarai, Ashoka (Array, 2020)
Akeel Bilgrami (2016) has argued against the scientistic method and its treatment of ethical values by declaring it a superstition of science for not considering values to be part of nature. This paper agrees with the concept of the engaged self discussed by Bilgrami in order to make sense of ethical values. However, it attempts to argue against the conceptual incoherence by juxtaposing value properties and the engaged self. The incoherence can be avoided by following a Wittgensteinian understanding of ethical values which has been explicated very briefly, yet in a significant way, in Tractatus Logico–Philosophicus and also in A Lecture on Ethics in some detail.